Peningkatan Kemampuan Leadership dan Public speaking melalui Literasi Bahasa Inggris pada Forum Cinta Muda Kota Medan - Yoni Rahayu; Muhammad Muslim Nasution; Soraya Grabiella Dinamika; Yurial Arief Lubis (Yayasan Literasi Sains Indonesia, 2025)
This Community Service Program (PKM) aimed to improve leadership and public speaking skills based on English literacy among members of Forum Cinta Muda Kota Medan. The activity was initiated in response to the limited ability of forum members to lead and communicate in public, particularly in English, which hampers their participation in both local and international forums. The program was conducted over two days using a participatory-educative method, involving participants actively through material delivery, practice sessions, simulations, and evaluations. The training materials included fundamental concepts of leadership, public speaking, the relationship between both skills, and presentation techniques in English. Participant abilities were evaluated through pre-test and post-test questionnaires. The analysis results showed a significant improvement in participant abilities, with an average N-gain score of 0.72, categorized as high. This improvement was evident in aspects such as knowledge of leadership principles, public speaking concepts, presentation stages, and confidence in delivering ideas in English. The program’s impact extends not only to individual participants but also strengthens the organizational capacity of Forum Cinta Muda in addressing global communication challenges. For sustainability, it is recommended to hold regular classes, internal competitions, and establish collaborations with English-speaking communities and related networks.